The use of manipulative teaching and learning aids and cooperative learning among mathematics slow learners - Chiam, Sun May (2013)
The mixed method study investigated if manipulative teaching and learning aids (MA) and cooperative learning structure function named "RoundRobin & AllWrite Consensus" (CL) were able to assist Year 2 Special Rehabilitation Program pupils to acquire better mastery in basic operations. The quantitative part employed quasi-experimental method with pretest-posttest design. The control groups were taught with flash cards; the Experimental 1 groups were intervened with counters; and the Experimental 2 groups were intervened with CL. Each group was intervened 30 minutes in 30 interventions for 12 weeks. Their achievement were evaluated through ANCOVA. The effects of the interventions were examined through effect size. The achievements of the groups in their pretest and posttest was compared; and the respondents' skills in the cognitive domain were" examined through analyses on item Response Model. Questionnaire was employed to examine the perceptions of the respondents on " motivation to learn", "fun in learning" and "confident to learn", The findings of the questionnaire were triangulated by reflective logs, field notes and the informal interviews. The merits and the deficiencies of the interventions were obtained through reflective logs, field notes and the informal interviews. The findings implied that MA and CL assisted the Year 2 Special Rehabilitation program pupils to acquire better mastery in basic operations. However, all the respondents still faced difficulties with the skill at application-transfer level after the interventions. The respondents had low perceptions on MA and they had high perceptions on CL. MA was found useful for facilitating teaching and learning at the earlier stage of the intervention only. CL was not able to facilitate teaching and learning at the beginning stage of the intervention but it was effective once the social relation was built among the respondents.